2007
DOI: 10.2527/jas.2006-741
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dry matter intake restriction on diet digestion, energy partitioning, phosphorus retention, and ruminal fermentation by beef steers

Abstract: Two experiments were conducted to determine the effects of DMI restriction on diet digestion, ruminal fermentation, ME intake, and P retention by beef steers. In Exp. 1, twelve Angus x steers (average initial BW = 450 +/- 18 kg) were assigned randomly to 1 of 3 diets that were formulated to promote a 1.6-kg ADG at intake levels corresponding approximately to 100% (ad libitum, AL), 90% (IR90), or 80% (IR80) of ad libitum DMI. In Exp. 2, twelve crossbred steers (average initial BW = 445 +/- 56 kg) fitted with ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
1
10
2
Order By: Relevance
“…The percentage of GEI lost as urine in food restrictions was higher, 4.1% compared to that shown in the ad libitum phase in F1 HxG animals, Gyr cows showed no difference between periods. [ 12 ], evaluating dry matter restriction levels like those of the present study (10 to 20%) reported increased energy lost as urine depending on the dietary restriction.…”
Section: Resultssupporting
confidence: 49%
See 2 more Smart Citations
“…The percentage of GEI lost as urine in food restrictions was higher, 4.1% compared to that shown in the ad libitum phase in F1 HxG animals, Gyr cows showed no difference between periods. [ 12 ], evaluating dry matter restriction levels like those of the present study (10 to 20%) reported increased energy lost as urine depending on the dietary restriction.…”
Section: Resultssupporting
confidence: 49%
“…The percentage of GE lost as feces was higher in F1 HxG (23.3%) compared to Gyr (20.7%), as occurred in the 1 st period ( Fig 1 ). [ 12 ], evaluating the scheduled dietary restriction in finishing steers, did not observe differences in the percentage of energy lost in the feces between the different restrictions, 10 and 20%, being these values lower than that presented in the ad libitum phase. MEI was similar among 2 nd , 3 rd and 4 th , being higher in F1 HxG in relation to Gyr.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Malnutrition causes imbalance in glucose homeostasis, and the decrease of insulin in circulation induces the reduction of feed intake in dairy cows [ 16 ]. Therefore, the feed intake reduction in IR cows might have inhibited the volatile fatty acid production in the rumen and thus suppressed gluconeogenesis in the liver [ 9 ]. Lower energy status, such as lower BCS, before calving of IR group in this study might be caused by long-term malnutrition from previous lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Residual feed intake was independent of BC in yearling ewes fed ad libitum or at a maintenance restricted feeding level (Redden et al, 2013). Clark et al (2007) fed steers at 3 levels of feed consumption (ad libitum or 90 or 80% of ad libitum) with a given ME intake. They concluded that improvements in feed efficiency by this manner of restriction do not appear to be related to changes in diet digestion or ME intake, similar to what was observed in the present study.…”
Section: Methodsmentioning
confidence: 99%